Analisis Keuntungan Industri Kecil Roti Allen di Kelurahan Tinoor satu Kecamatan Tomohon Utara - Liberty Kaparang; Grace A.J. Rumagit; Ribka M. Kumaat; Ellen G. Tangkere (Universitas Sam Ratulangi, 2014)
ABSTRACTLiberty Kaparang. Analysis of Advantage of Small Industry â€œAllenâ€ Bread. (Under Guidance of Grace. A.J. Rumagit, as Chairman ; Ribka. M. Kumaat, ; Ellen. G. Tangkere as members.Agricultural and industrial sectors are the two sectors that play an important role in the Indonesian economy. As a mainstay in economic development, the sector is expected to contribute in improving the equitable and income for the community.The objective of this research is to analyze how the benefits received in theâ€œAllenâ€ bakery industry in Tinoor Village, North Tomohon Sub District in one process of production. The research conducted for approximately three months, and the data collected in the form of primary data were taken directly from the owner of the â€œAllenâ€ bakery industry in Tinoor village, North Tomohon Sub District.The research result showed that the average profit made by small industries in one process of production was Rp. 2,899,509, with an average cost of Rp 2,300,491 from an average of 4,000 packs of bread production at a price of Rp 800 and Rp.1800.Revenue Cost Ratio Analysis showed that the â€œAllenâ€ bakery industry in Tinoor village its R/C was 2,2 or itâ€™s ratio was greater than one or the industry obtained profit. In this bread industry, the revenue was greater than cost, therefore the industry could get profit the use for the next production.